Effect of sodium chloride reduction on physicochemical, biochemical, rheological, structural and sensory characteristics of Tybo cheese - Sihufe, Guillermo Adrian (2018)
Tybo cheeses with different salt contents (0.46, 0.91, 1.28 g NaCl 100 g−1 cheese) at different ripening times (1, 14, 26, 40 days of ripening) were evaluated for the effect of salt reduction on physicochemical, biochemical, rheological, structural and sensory characteristics. Reducing salt (from 1.28 g NaCl 100 g−1 cheese; cheese C3) by 30% (cheese C2) or 65% (cheese C1) resulted in a significant increase in moisture content, maturation index, αS1-I-casein degradation, chromatographic area of water-soluble fraction at pH 4.6; the level of total intact caseins decreased significantly. Rheological parameters significantly decreased with salt reduction; cheeses C3 had smaller voids than those of samples C1 and C2. Generally, flavour and texture attributes showed similar profiles for the different salting conditions; salty, acid and overall persistence significantly decreased with salt content. Overall, the reduction of 30% salt content resulted in a cheese similar to a typical Tybo cheese in most respects.